2‐Methoxyestradiol attenuates chronic‐intermittent‐hypoxia‐induced pulmonary hypertension through regulating microRNA‐223. Issue 5 (24th September 2018) - Hao, Shengyu; Jiang, Liyan; Fu, Cuiping; Wu, Xu; Liu, Zilong; Song, Jieqiong; Lu, Huan; Wu, Xiaodan; Li, Shanqun
Abstract: Pulmonary hypertension (PH) is prevalent in patients with obstructive sleep apnea (OSA) syndrome, and coexistence of PH and OSA indicates a worse prognosis and higher mortality. Chronic intermittent hypoxia (CIH) is the key pathogenesis of OSA. Also, microRNA‐223 (miR‐223) plays a role in the regulation of CIH‐induced PH process. However, the detailed mechanism of CIH inducing PH is still unclear. This study aimed to investigate the pathological process of CIH associated PH and explore the potential therapeutic methods. In this study, adult Sprague–Dawley rats were exposed to CIH or normoxic (N) conditions with 2‐methoxyestradiol (2‐Me) or vehicle treatment for 6 weeks. The results showed that 2‐Me treatment reduced the progression of pulmonary angiogenesis in CIH rats, and alleviated proliferation, cellular migration, and reactive oxygen species formation was induced by CIH in pulmonary artery smooth muscle cells (PASMCs). CIH decreased the expression of miR‐223, whereas 2‐Me reversed the downregulation of miR‐223 both in vivo and in vitro. Furthermore, the antiangiogenic effect of 2‐Me observed in PASMCs was abrogated by miR‐223 inhibitor, while enhanced by miR‐223 mimic. These findings suggested that miR‐223 played an important role in the process of CIH inducing PH, and 2‐Me might reverse CIH‐induced PH via upregulating miR‐223. Abstract : The role of 2‐methoxyestradiol (2‐ME) was investigated in a model of pulmonary hypertension (PH) induced by chronic intermittent hypoxia. We found that 2‐ME markedly reduced PH progression, and this effect is associated with reduced microRNA‐223 (miR‐223).